PENGARUH DEWAN KOMISARIS INDEPENDEN TERHADAP KUALITAS LABA DENGAN KONSENTRASI KEPEMILIKAN SEBAGAI VARIABEL PEMODERASI - Farida, Dessy Noor (PRESTASI, 2012)
The Quality of earning is element that is often used by investors to take investment decisions. But the financial scandals that occurred, causing investors have crisis confidence in capital markets. Therefore, the necessary existence of a good corporate governance is very importance to create a financial statement that reflects the real condition of the company. The purpose of this study is to analyze the influence of independence board of commisioners on earnings quality which are moderated by the concentration of family ownership. Manufacturing firms listed in Indonesian Stock Exchange 2007-2009 is the object of this study. Based on purposive sampling technique, it gets 118 firms. Multiple regression analysis using SPSS program. The result of the hypothesis test indicates that independent board of commissioners have significantly positive effect on discretionary accruals. This study also found a concentration of family ownership has insignificantly moderates the effect on an independent board to discretionary accruals. Keywords: Discretionary Accruals, independent board of commisioners, family ownership